Anxiety disorders among adolescents and young adults: Prevalence and mental health care service utilization in a regional epidemiological study in Germany. (October 2021) - Niermann, Hannah C.M.; Voss, Catharina; Pieper, Lars; Venz, John; Ollmann, Theresa M.; Beesdo-Baum, Katja
Highlights: More than 1/5 of adolescents and young adults meet criteria for a lifetime DSM-5 anxiety disorder. Only about 1/3 of adolescents and young adults with an anxiety disorder consult mental health care. Most often they consult an outpatient psychotherapist/psychologist. Having a comorbid disorder or being female increases the likelihood of seeking help. Explicit need to improve recognition and intervention efforts for youth with anxiety disorders. Abstract: Background: Anxiety disorders are among the most prevalent mental disorders. While it is known that a majority of individuals with anxiety disorders remains untreated, actual treatment rates for adolescents and young adults in Germany remain largely unknown. Methods: As part of the Behavior and Mind Health (BeMIND) study, examining a random community sample of 14–21-year-olds (Dresden; Germany; N = 1, 180), the lifetime prevalence for DSM-5 anxiety disorders and lifetime service utilization rates were determined by a standardized interview (DIA-X-5/CIDI). Results: In the present sample, 23.3 % of adolescents and young adults fulfilled DSM-5 criteria for at least one lifetime anxiety disorder. Of those, 39.1 % used any health care services, most frequently they visited an outpatient psychotherapist/psychologist (23.0 %). Individuals with agoraphobia were most likely to use any in- or outpatient specialized service (64.8 %), while individuals with a specific phobia were least likely (22.3 %). Having a comorbid disorder or being female increased the likelihood of seeking help. Conclusion: The results showed that approximately 2/3 of adolescents and young adults suffering from an anxiety disorder did not seek help and only few report contacts with a psychotherapist. Given the adverse long-term consequences of anxiety disorders, these findings suggest to improve efforts on increasing intervention awareness and treatment possibilities for these individuals.